Odpowiedzi

2010-02-22T16:06:29+01:00
A) ∑ x+3y=3
∑ x-y=5

x=3-3y
3-3y-y=5

x=3-3y
-4y=2

x=3-3y
y=-1/2

x=3-3*(-1/2)=3+1,5=4,5

b) ∑ 2x-y=10
∑ x+5y= -17

2x-y=10
x=-17-5y

2(-17-5y)-y=10
x=-17-5y

-34-10y-y=10
x=-17-5y

-11y=44
x=-17-5y

y=-4
x=-17-5*(-4)=-17+20=3

c) ∑3m+n=10
∑2m-5n= -11

n=10-3m
2m-5n=-11

n=10-3m
2m-5(10-3m)=-11

n=10-3m
2m-50+15m=-11

n=10-3m
17m=39

n=10-3m
m=39/17
n=10-3*39/17=53/17

d) ∑ 4a-2=b
∑ 3a+7b= 1,5

4a-2=b
3a+7(4a-2)=1,5

b=4a-2
3a+28a-14=1,5

b=4a-2
31a=15,5

b=4a-2
a=0,5
b=4*0,5-2=2-2=0
2010-02-22T16:12:51+01:00
1]
x+3y=3
x-y=5

x+3y=3
x=5+y

5+y+3y=3

4y=3-5
4y=-2
y=-2:4
y=-½
x=5+(-½)=4½
spr, 4½+3×(-½)=3
4½-1½=3
3=3
2]
2x-y=10
x+5y=-17

y=2x-10
x+5(2x-10)=-17

x+10x-50=-17
11x=-17+50
11x=33
x=33:11
x=3
y=2×3-10=6-10=-4
spr. 3+5×(-4)=-17
320=-17
-17=-17
3]
3m+n=10
2m-5n=-11

n=10-3m
2m-5(10-3m)=-11
2m-50+15m=-11
17m=-11+50
17m=39
m=2⁵/₁₇

n=10-3×2⁵/₁₇
n=10-6¹⁵/₁₇
n=3²/₁₇
spr. 2׳⁹/₁₇-5 razy⁵³/₁₇=-11
-11=-11
4]
4a-2=b
3a+7b=1,5

3a+7(4a-2)=1,5
3a+28a-14=1,5
31a=1,5+14
31a=15,5
a=15,5:31
a=0,5
b=4×0,5-2=0
spr. 3×0,5+0=1,5
1,5=1,5
Najlepsza Odpowiedź!
2010-02-22T16:30:15+01:00
A)
x+3y=3
x-y=5

x = 3 - 3y
3 - 3y - y = 5

x = 3 - 3y
-4y = 2 /:(-4)

x = 3 - 3y
y = - 1/2

x = 3 - 3* (-1/2)
y = -1/2

x = 3 + 3/2
y = -1/2

x = 4,5
y = -0,5

b)
2x-y=10
x+5y= -17

y = 2x - 10
x + 5*(2x - 10) = -17

y = 2x - 10
x + 10x - 50 = -17

y = 2x - 10
11x = 33 /:11

y = 2x - 10
x = 3

y = 2* 3 - 10
x = 3

y = -4
x = 3

c)
3m+n=10
2m-5n= -11

n = 10 - 3m
2m - 5 * (10 - 3m) = -11

n = 10 - 3m
2m - 50 + 15m = -11

n = 10 - 3m
17m = 39 /: 17

n = 10 - 3m
m = 39/17

n = 10 - 3m
m = 2 i 5/17

n = 10 - 3* 39/17
m = 2 i 5/17

n = 170/17 - 117/17
m = 2 i 5/17

n = 53/17
m = 2 i 5/17

n = 3 i 2/17
m = 2 i 5/17

d)
4a-2=b
3a+7b= 1,5

b = 4a - 2
3a + 7*(4a - 2) = 1,5

b = 4a - 2
3a + 28a - 14 = 1,5

b = 4a - 2
31a = 15,5 /: 31

b = 4a - 2
a = 0,5

b = 4* 0,5 - 2
a = 0,5

b = 2 -2
a = 0,5

b = 0
a = 0,5